Determinan Tuberkulosis pada Balita di Indonesia (Analisis Data Survei Status Gizi Indonesia Tahun 2024) - Resa Triani; Defriman Djafri; Mery Ramadani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Tuberculosis (TB) was still a major public health challenge in Indonesia, a country that bore the second‑highest global burden of the disease. Cases among toddlers continued to be a significant public health concern because of their greater vulnerability to infection. The rising prevalence of pediatric TB, along with its complex risk factors, highlighted the need to identify the main determinants driving TB occurrence in this age group. The present study investigated factors associated with TB in toddlers across all 38 provinces of Indonesia. Data from the 2024 Indonesian Nutritional Status Survey (SSGI) were used in the analysis, and survey weights were applied following official SSGI guidelines. A cross‑sectional design was adopted, and the sample consisted of 246,338 toddlers. The dependent variable was TB occurrence, whereas the independent variables included child age, nutritional status, stunting, BCG vaccination status, history of exposure to TB patients, low birth weight, employment status of both parents, and household density. Data analysis was carried out in three stages: univariate analysis, bivariate analysis using simple logistic regression, and multivariate analysis using multiple logistic regression. Results from the bivariate analysis indicated that nutritional status, stunting, BCG vaccination, TB exposure history, and low birth weight were significantly associated with TB occurrence. In the multivariate model, a history of TB contact was identified as the most dominant determinant, yielding a prevalence odds ratio (POR) of 46.62 (95% CI: 37.13–58.54).